Microstructure and dielectric properties of bismuth germanate glass-ceramics - Kantha P. (2014)
Bismuth germanate composites containing Bi2GeO 5-Bi4Ge3O12 phases were prepared by glass ceramic method and sintering techniques. The existences of three bismuth germanate crystals of Bi2GeO5, Bi4Ge 3O12 and BiBO3 were found in XRD patterns. The amount of each phase depended mostly on the sintering temperature where the Bi4Ge3O12 phase was found to increase with increasing sintering temperature. The mixing of round and pyramidal shape crystals was observed in the sample sintered at 650°C. This gave rise to the improvement in its dielectric properties where the εr was found to increase from ∼78 to ∼395 for the sample sintered at 500°C and 650°C, respectively. Moreover, the tanδ was found to decrease greatly with increasing sintering temperature. Thus, this Bi2GeO 5-Bi4Ge3O12 composite may be considered as a promising candidate of microwave dielectric materials. Copyright © Taylor & Francis Group, LLC.